(3feGPL JWHjbjI dCYeGd GdebGhdGJ hGdeTQhYGJ GdUfGYjI hGdRQGYjIs - (3VjGA(B, (3WeGfs ((3GdbGgQI(B:s (3ecJHI eOHhdj(B,s, 1999)
(3CeKdI dfeGPL JWHjbjI dCYeGd GdebGhdGJ hGdeTQhYGJ GdUfGYjI hGdRQGYjIs
(3ehLg ddebGhdjf, dCUMGH GdeTQhYGJ GdEfJGLjI, ddegfOSjfs
Keywords: (3EOGQI GdeTQhYGJs; (3GdeTGQjY GdEfJGLjIs; (3eMGSHI GdJcGdjas